2021
DOI: 10.1186/s13690-021-00695-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral self-care behavior and its influencing factors in a sample of school children from Central Iran

Abstract: Background Oral health is an important part of public health and crucial to health promotion and enhancing the quality of life. This research examined childhood oral self-care behavior and their related factors using extended Theory of Planned Behavior (TPB). Method This cross-sectional study was conducted on 368 sixth-grade elementary school students in Saveh city, Iran, in 2019. The students were selected using a random multi-stage sampling metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
3
0
2
Order By: Relevance
“…The comparison of mean scores of behavioral intention before and after the intervention showed a significant difference between the two groups, which was in line with the results of Zareban et al, (2021) [ 32 ], Shitu et al, (2021) [ 10 ], and Karimi et al, (2020) [ 33 ]. In other words, the results of the present study indicated that training and encouraging individuals to dental and oral self-care affect their behavioral intention for dental and oral self-care.…”
Section: Discussionsupporting
confidence: 89%
“…The comparison of mean scores of behavioral intention before and after the intervention showed a significant difference between the two groups, which was in line with the results of Zareban et al, (2021) [ 32 ], Shitu et al, (2021) [ 10 ], and Karimi et al, (2020) [ 33 ]. In other words, the results of the present study indicated that training and encouraging individuals to dental and oral self-care affect their behavioral intention for dental and oral self-care.…”
Section: Discussionsupporting
confidence: 89%
“…Our study shows that about half of the students know a brushing technique, but 81.75% know that brushing removes bacterial plaque, the results obtained being similar to the results of other specialized studies [ 34 , 50 , 54 ]. In order to receive individualized information on oral hygiene, it is recommended to take into account the provision of access to specialized dental services [ 44 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it is insufficient for TPB to explain a complicated psychological mechanism. So many studies modified TPB to add important factors to explain or predict specific behaviors (21)(22)(23). And Ajzen further suggested that the TPB was open to further expansion if additional predictors could be identified that explained more variance when included (24).…”
Section: Introductionmentioning
confidence: 99%